Modelling insulated coving's potential to reducing thermal bridging and moisture risk in solid wall dwellings retrofitted with external wall insulation. (May 2017) - Glew, David; Brooke-Peat, Matthew; Gorse, Christopher
Abstract: Mould growth and surface condensation are problems for many dwellings, and the retrofitting of insulation can increase the risk of these occurring. This is especially the case for historical solid wall properties receiving external wall insulation (EWI), which often have architectural details at the roof eaves that cause discontinuities in the insulation and so can result in excessive thermal bridging. This paper presents the results of an investigation into retrofitted solid wall properties where modelling is used to investigate the problem and effectiveness of insulated coving products which are designed to reducing thermal bridging. Thermal modelling is undertaken to establish the optimum design to reduce risk. The insulated coving was found to be effective in reducing thermal bridging in all the scenarios investigated and to reduce moisture risks occurring in some solid walls situations. Highlights: External wall insulation does not always extend to roof eaves due to architectural features or particular roof details. Excessive thermal bridging and increased risk of mould growth can occur in solid wall properties where this occurs. Changes in conditions in solid wall properties with and without EWI when an insulated coving product are quantified. Insulated coving can reduce thermal bridging and improve the surface temperature factors in properties with EWI.